Empirical Analysis of the Effect of Board of Commissioners and Profitability on Corporate Social Disclosure: Profit Management as Mediation - Kiryanto, Kiryanto; Ummah, Fatuwa Tul (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2024)
This study aims to analyze the impact of mediating earnings management on the relationship between corporate governance, profitability and corporate socials responsibility. Specifically analyzing the impacts of the boards of commissioners on corporate social responsibility and earning management and the impact of earnings management on corporates social responsibility. The population of this research is a manufacturing company listed on the Indonesia Stock Exchange (IDX) with a purposive sampling technique and obtained a sample of 63 with 189 data. The results show that profitability has a negative effect on earning management. Likewise, the boards of commissioner and profitability have a significant positive effect on Corporate Social Responsibility (CSR). Meanwhile the board of commissioners and earnings management have no effect on corporate social responsibility. Earnings management is also unable to mediate the relationship between the board of commissioners and profitability to corporate social responsibility. This research contributes to the field of accounting, especially to the theory of how the relationship between corporate governance, profit management and corporate social responsibility. The results of this study also contribute to the importance of profit for the company in order to increase the company's corporate social responsibility.